Comparative Myocardial Deformation in 3 Myocardial Layers in Mice by Speckle Tracking Echocardiography. (2nd March 2015) - Tee, Nicole; Gu, Yacui; Murni,; Shim, Winston
Abstract : Background . Speckle tracking echocardiography (STE) using dedicated high-resolution ultrasound is a relatively new technique that is useful in assessing myocardial deformation in 3 myocardial layers in small animals. However, comparative studies of STE parameters acquired from murine are limited. Methods . A high-resolution rodent ultrasound machine (VSI Vevo 2100) and a clinically validated ultrasound machine (GE Vivid 7) were used to consecutively acquire echocardiography images from standardized parasternal long axis and short axis at midpapillary muscle level from 13 BALB/c mice. Speckle tracking strain (longitudinal, circumferential, and radial) from endocardial, myocardial, and epicardial layers was analyzed using vendor-specific offline analysis software. Results . Intersystem differences were not statistically significant in the global peak longitudinal strain (−16.8 ± 1.7% versus −18.7 ± 3.1%) and radial strain (46.8 ± 14.2% versus 41.0 ± 9.5%), except in the global peak circumferential strain (−16.9 ± 3.1% versus 27.0 ± 5.2%, P < 0.05 ). This was corroborated by Bland Altman analysis that revealed a weak agreement in circumferential strain (mean bias ± 1.96 SD of −10.12 ± 6.06%) between endocardium and midmyocardium. However, a good agreement was observed in longitudinal strain between midmyocardium/endocardium (mean bias ± 1.96 SD of −1.88 ± 3.93%) and between midmyocardium/epicardium (mean bias ± 1.96 SD of 3.63 ± 3.91%). Radial strain (mean bias ± 1.96 SD of −5.84 ± 17.70%) had wide limits of agreement between the two systems that indicated an increased variability. Conclusions . Our study shows that there is good reproducibility and agreement in longitudinal deformation of the 3 myocardial layers between the two ultrasound systems. Directional deformation gradients at endocardium, myocardium, and epicardium observed in mice were consistent to those reported in human subjects, thus attesting the clinical relevance of STE findings in murine cardiovascular disease models.